Offshore freshwater aquifers: Toward equitable distribution - Martin‐Nagle, Renée (Wiley interdisciplinary reviews. Water, 2020)
Legal principles and practices for determining ownership and control of seabed resources have been crafted and honed by various parties throughout the 20th century, often on an ad hoc basis to meet specific situations and sectoral needs. The legal landscape for offshore freshwater aquifers consequently spans domestic, regional, and international regimes, making the governance analysis for this untapped resource complex and multilayered. At the apex of ocean governance lies the UN Convention on the Law of the Sea (LOSC), a global treaty with almost universal application. Both LOSC and customary law grant each coastal state exclusive sovereign rights over seabed natural resources in its continental shelf, although those rights are limited by other legal commitments such as obligations to protect the environment. LOSC does not address transboundary resources, but early and sustained demand for offshore hydrocarbons caused that governance gap to be filled through judicial decisions, bi‐lateral treaties, and customary practices. Traditionally, distribution of natural resources has been viewed as a right commensurate with sovereign claims to the resource, but a strong ethical argument can be made for treating water as an exceptional case due to its uniquely life‐giving properties. When offshore freshwater is eventually appropriated for use, humanity will have an opportunity to choose between following old patterns of distribution or crafting a more inclusive system. In a world facing global shortages of freshwater due to pollution, overuse and climate change, policymakers designing a legal regime for untapped reservoirs of a vital resource for which there is no substitute should consider more equitable forms of distribution. Both Roman law and LOSC provide precedents for sharing natural resources, and the emerging trend of benefit‐sharing offers multiple and varied possibilities as well. This article is categorized under: Human Water > Water Governance Human Water > Rights to Water Coastal and maritime areas are subject to overlapping international, regional and domestic governance regimes